SUSTAINABILITY ACCOUNTING IN THE PUBLIC SECTOR: INTEGRATING ESG METRICS INTO GOVERNMENT REPORTING SYSTEMS - Loso Judijanto; Muhammad Sani Kurniawan; Rara Silkfan (CV. Adiba Aisha Amira, 2026)
The adoption of sustainability accounting in the public sector is becoming increasingly important amidst rising demands for transparency, accountability, and sustainability in the management of government resources. Integrating Environmental, Social, and Governance (ESG) indicators into government reporting systems offers a strategic approach to augmenting financial information with non-financial aspects that reflect social and environmental impacts as well as governance quality. This study aims to analyze the concepts and evolution of sustainability accounting implementation in the public sector and to examine the role of ESG metric integration in enhancing the quality of government reporting systems. A literature review methodology was employed, analyzing various scholarly articles, institutional reports, and academic publications relevant to sustainability accounting, ESG, public sector reporting, and sustainable governance. The findings indicate that integrating ESG metrics can strengthen the transparency of government reporting by providing comprehensive information on resource utilization, environmental impacts, social benefits, and governance quality. Such implementation also holds the potential to support sustainability-driven decision-making, enhance public accountability, and bolster stakeholder trust in government institutions. However, implementation faces challenges, including a lack of standardized ESG indicators, limitations in data quality and availability, human resource capacity constraints, and the need to harmonize reporting standards. Therefore, an integrated, measurable, and adaptive ESG reporting framework for the public sector is essential to ensure that sustainability accounting becomes a strategic component of government reporting systems and supports the achievement of sustainable development goals.